2018
DOI: 10.1136/jmedgenet-2017-105146
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping MHC associations in Graves’ disease and its clinical subtypes in Han Chinese

Abstract: BackgroundThe classical human leucocyte antigen (HLA) genes were the most important genetic determinant for Graves’ disease (GD). The aim of the study was to fine map causal variants of the HLA genes.MethodsWe applied imputation with a Pan-Asian HLA reference panel to thoroughly investigate themajor histocompatibility complex (MHC) associations with GD down to the amino acid level of classical HLA genes in 1468 patients with GD and 1490 controls of Han Chinese.ResultsThe strongest finding across the HLA genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…In Chinese patients with GD, Lys66, Arg69, and Val76 of HLA-B were identified, which were present in HLA-B*46:01 in our data. Tyr116 of HLA-C, which was present in HLA-C*01:02 in our data, was also proven to be associated with GD in Chinese [24]. Ser57 of HLA-DRB1, which was associated with GD in our data, has been reported to be associated with Primary Sjogren's syndrome in a Chinese study [25].…”
Section: Discussionsupporting
confidence: 64%
“…In Chinese patients with GD, Lys66, Arg69, and Val76 of HLA-B were identified, which were present in HLA-B*46:01 in our data. Tyr116 of HLA-C, which was present in HLA-C*01:02 in our data, was also proven to be associated with GD in Chinese [24]. Ser57 of HLA-DRB1, which was associated with GD in our data, has been reported to be associated with Primary Sjogren's syndrome in a Chinese study [25].…”
Section: Discussionsupporting
confidence: 64%
“…(10) Several GWA studies in different autoimmune diseases have identified significant associations of different ANAs with specific polymorphisms and classical HLA alleles. (28)(29)(30) Previously, two studies investigated the association of specific HLA class I and II alleles with ANAs in PBC, but these studies have been confined to small sample sets and limited HLA alleles. (31,32) The results presented in this report also have merits over previous reported imputations in other HLA fine-mapping studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the mentioned COVID-19 study ( Warren and Birol, 2020 ), HLA class II alleles DPA1*02:02 and DPB1*05:01 were found to be frequent as well. Those alleles are common in Han Chinese and associated with autoimmune diseases Graves' ( Chu et al., 2018 ) and narcolepsy ( Ollila et al., 2015 ). The latter one, DPB1*05:01, is associated with chronic hepatitis B in Asians, in addition to being a risk factor effecting viral infection clearance ability (( Kamatani et al., 2009 ; Ollila et al., 2015 ) cited in ( Middleton et al., 2003 )).…”
Section: Discussionmentioning
confidence: 99%